The Substrate and Urban Transformation. Rome: The Formative Process of the Pompeo Theater Area - CRISTIAN SAMMARCO (Journal of Contemporary Urban Affairs, 2019)
The city is an organism that has been transformed through continuous modifications of its form. In these transformations, we can find traces that remain and organize the successive urban aggregates over time. The case that will be proposed is one of the urban fabric formed in the area of Pompeo’s theatre, in the Renaissance district of Rome. Through Saverio Muratori’s studies on the urban history of Rome and the new archaeological discoveries, the formation of a residential building on the remains of the ancient building until its specialization was analyzed. The role of the substratum, evident in this case study, shows how spontaneous architecture attests to the great forms of the past, and reuses them in every era, transforming and reinterpreting them. In this way, the city is so eternal reuse of its forms, its paths and its materials.